7. According to Mean Value Theorem, there must exist "c" s.t. "f'(c) = \\frac{f(b) - f(a)}{b - a}" . In our case, "f'(x) = 3 (x+1)^2" , and "f(1) = 8, f(-1) = 0" , hence one has to solve quadratic equation "3 (c+1)^2 = 4" for "c" . Obtain: "c = \\frac{-3 \\pm 2 \\sqrt{3}}{3} = \\frac{-\\sqrt{3} \\pm \\sqrt{2}}{\\sqrt{3}}" , so the answer is b).
8 "f'(x) = x^2 - x - 2 + x(2 x - 1) = 3 x^2 - 2 x - 2" . The function is obviously continuous and differentiable in "[-1,1]", so we can apply Mean Value Theorem: "f'(c) = 3 c^2 - 2 c - 2 = \\frac{f(1) - f(-1)}{2} = \\frac{-2 - 0}{2} = -1" . Solving for "c" , obtain "c = -\\frac{1}{3}, c = 1", so the answer is a).
Comments
Dear Lawal. Please use the panel for submitting new questions.
Compute the first thrre derivatives of \\(f(x)=2x^{5}+x^{\\frac{3}{2}}-\\frac{1}{2x}\\)
Leave a comment